Modulation of vagal activity may help reduce neurodevelopmental damage in the offspring of mothers with pre-eclampsia - Abarca-Castro, Eric Alonso; Talavera-Peña, Ana Karen; Reyes-Lagos, José Javier; Becerril-Villanueva, Enrique; Pérez-Sanchez, Gilberto; de la Peña, Francisco R.; Maldonado-García, José Luis; Pavón, Lenin (Frontiers in Immunology, 2023)
Maternal Immune Activation (MIA) has been linked to the pathogenesis of pre-eclampsia and adverse neurodevelopmental outcomes in the offspring, such as cognitive deficits, behavioral abnormalities, and mental disorders. Pre-eclampsia is associated with an activation of the immune system characterized by persistently elevated levels of proinflammatory cytokines, as well as a decrease in immunoregulatory factors. The Cholinergic Anti-inflammatory Pathway (CAP) may be a great help in regulating the maternal inflammatory response during pre-eclampsia and protecting the developing fetus from inflammation-induced damage. Dysregulation in CAP has been associated with the clinical evolution of pre-eclampsia. Some studies suggest that therapeutic stimulation of this pathway may improve maternal and fetal outcomes in preclinical models of pre-eclampsia. Vagus Nerve Stimulation (VNS) modulates the CAP, improving maternal hemodynamics, limiting the inflammatory response, and promoting the growth of new neurons, which enhances synaptic plasticity and improves fetal neurodevelopment. Therefore, we postulate that VNS may improve maternal and fetal outcomes in pre-eclampsia by targeting underlying immune dysregulation and promoting better fetal neurodevelopment. In this perspective, we explore the clinical and experimental evidence of electrical, pharmacological, physical, and biological stimulation mechanisms capable of inducing therapeutical CAP, which may be applied in pre-eclampsia to improve the mother's and offspring's quality of life.